Citizen-Centered Generative AI for Urban Transformation: The AI Copacabana Demo Case - Schiavo, Fabienne; Freitas de Magalhães, Claudio (Street Art & Urban Creativity, 2025)
This paper presents the development and real-world testing of AI Copacabana, a customized virtual assistant designed to operationalize the Innovation Model for Smart Sustainable Cities (ISC Model) by connecting the Local Innovation Map (LIM) with citizen-led actions. Validated at TRL5 in Copacabana, the prototype demonstrates how AI can act as a bridge between territorial diagnoses and community-driven initiatives—solutions that are decentralized, aligned with sustainable urban development goals, and integrated to impact local quality of life positively. Embedding a culturally familiar AI tool within participatory frameworks, the study illustrates new pathways for scalable, people-centered smart cities and sustainable urban innovation.